Unexpected Small-Bowel Finding in Overt-Obscure Gastrointestinal Bleeding in a Patient with Neurofibromatosis Type 1 and Crohn’s Disease - Gomes,Catarina (2022)
Abstract Gastrointestinal stromal tumors (GIST) are the most frequent mesenchymal neoplasms affecting the gastrointestinal tract, and the small bowel is the second most frequent location. Approximately 5% of patients with GIST are not sporadic and have a familial autosomal dominant syndrome, such as neurofibromatosis type 1 (NF1). Gastrointestinal bleeding is a common presentation of GIST, and lesions such as submucosal tumors may be detected more readily by capsule endoscopy due to luminal impingement and overlying ulceration. Our report emphasizes the importance of small-bowel investigation in patients with Crohn’s disease and NF1 presenting with recent overt bleeding.